Effect of Storage Methods and Seed Rhizome Treatment on Field Performance of Ginger var. Humnabad - SHADAP, A.; HEGDE, N. K.; LYNGDOH, Y. A.; RYMBAI, H. (Indian Journal of Hill Farming, 2015)
An experiment was conducted to evaluate the effect of different storage methods and seed rhizome treatment on the field performance of ginger var. Humnabad. The study included four storage methods viz., rhizomes kept in sand layers, 250 gauge polyethylene bag with 0.5% vents, Zero energy cool chamber (ZECC) either in open condition or in polyethylene bag with 0.5% vents. The seed rhizomes are treated with three different levels viz., Ridomil MZ (3g/l), Trichoderma harzianum (5g/kg seed rhizome) and control (no seed treatment). Highest sprouting percentage (98.89%), plant height (52.3 cm), leaf area index (25.75), number of tillers per clump (19.7), pseudostem girth (3.41 cm) and fresh rhizome yield (22.35 t/ha) was recorded in rhizome stored in ZECC treated with Trichoderma harzianum whereas, the rhizome stored in sand layer with no seed treatment recorded the lowest germination percentage (75.56%), plant height (33.6 cm), leaf area index (9.73), number of tillers per clump (12.6), pseudostem girth (2.32 cm) and fresh rhizome yield (11.84 t/ha).